Development of a Digital Integrated Science Teaching Module Based on Problem-Based Learning to Enhance Critical Thinking Skills Among Elementary School Students in Grade 3 - Indah Wulandari; Arie Rakhmat Riyadi; Asep Saefudin (Universitas Trunojoyo Madura, 2026)
This study was motivated by students’ lack of critical thinking skills, as well as the introduction of a new curriculum and the Pancasila Student Profile, which necessitate the development of teaching modules to cultivate these skills. Based on this, the study aims to develop a digital IPAS teaching module based on problem-based learning to enhance the critical thinking skills of elementary school students in Phase C. The research method used is the Design and Development method through five stages, namely analyze, design, development, implementation, and evaluation, abbreviated as ADDIE. Data collection techniques were conducted through interviews, validation questionnaires, and tests. The data analysis techniques in this study used qualitative and quantitative data analysis. The subjects of this study were fifth-grade elementary school students. The evaluation results from subject matter experts were 92.2%, media experts 85.4%, and instructional design experts 91.2%, all categorized as “highly suitable.” The product pilot test yielded an average improvement in scores between the pre-test and post-test. Additionally, the N-gain test resulted in a value of 0.93, meeting the criteria for effectiveness. Based on these findings, the digital IPAS teaching module based on Problem-Based Learning is suitable for use and capable of improving the critical thinking skills of elementary school students in Phase C.